(untitled) (Bangladesh Journal of Agriculture, 2023)
A field experiment was conducted in the research field of Sher-e-Bangla Agricultural University (SAU), Dhaka, Bangladesh to study variability and heritability in Brassica rapa L. for developing short durable, high yielding varieties. The experiment had laid out in a randomized complete block design with three replications and consisted of seven genotypes viz., G1 (BARI Sarisha-14), G2 (Brown Special), G3 (Yellow Special), G4 (Tori-7), G5 (BARI Sarisha-17), G6 (BARI Sarisha-15) and G7 (BARI Sarisha-6). The result revealed that G7 had the highest yield plant-1 (6.91 g) and longest duration (108.00 days) while G4 had the lowest yield plant-1 (4.12 g) and G2 had the shortest duration (79.33 days). High genotypic and phenotypic coefficient of variation for number of secondary branches plant-1 (95.35% and 99.39%), number of siliqua plant-1 (29.52% and 30.23%), plant height (25.19% and 25.38%) and number of seeds siliqua-1 (26.76% and 27.12%) had estimated. High heritability with high genetic advance and gain had observed for days to 80% maturity (99.92%, 20.99% and 23.36 %), plant height (98.55%, 53.99% and 51.53%) and number of siliqua plant-1 (95.33%, 101.25% and 59.37%). While high heritability with low genetic advance and high genetic gain were observed for number of primary branches plant-1 (92.02%, 0.70% and 188.43%), number of secondary branches plant-1 (92.02%, 7.47% and 188.43%), length of siliqua (98.23%, 1.104% and 29.96), 1000 seed weight (84.61%, 1.23% and 32.01%) and yield plant-1 (97.41%, 2.01% and 38.47%). Days to 80% maturity, plant height and number of siliqua plant-1 showed high heritability with high genetic advance and genetic gain indicated additive gene action and selection could be useful for these traits. While high heritability with low genetic advance had observed for number of primary and secondary branches plant-1, length of siliqua, 1000 seed weight and yield plant-1 indicated non additive gene action and selection might be ineffective for these traits. Bangladesh J. Agri. 2023, 48(2): 106-118